Perceptions And Experiences Of Prospective Brides And Grooms And Ora Officers Regarding The Use Of “Suscatinting” Application - Lela Hartini; Betty Yosephin Simanjuntak; Diah Eka Nugraheni (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Efforts to prevent stunting should begin in the preconception stage, especially among prospective married couples. The SusCatinTing (Premarital Course for Stunting Prevention) application is a digital-based intervention designed to improve the knowledge and experiences of prospective couples, especially regarding the First 1,000 Days of Life. It offers educational content of healthy pregnancies, maternal nutrition, and the concept of a harmonious family. To ensure inclusivity, the application features audio-based learning for users with visual impairments or limited literacy, alongside a Google Maps integration to help locate the nearest Office of Religious Affairs (ORA). This study aims to explore the perceptions, experiences of prospective brides and grooms in using the SusCatinTing application. Method: This study used a qualitative design to understand the phenomenon perception and experience. The research stages are systematically structured, starting with identifying informants, data collection, analysis, and drawing conclusions. Data collection was conducted through in-depth interviews and observations. Informants were selected purposively according to predetermined criteria so that the obtained can support the achievement of the research objectives. Each ORA was represented by one couple as the main informants. Supporting informants consisted of one marriage registrar, one marriage registration officer, and one Head of ORA from each selected office. Result: Almost all prospective couples participated in scheduled premarital guidance sessions conducted by the ORA. While many had heard of stunting previously, few were aware of it through the ORA. Most respondents were unfamiliar with SusCatinTing until they saw promotional posters during their marriage registration process. All respondents reported the app to be user-friendly, though it requires an internet connection. Conclusion: The findings suggest that the SusCatinTing application is a highly effective digital tool. It serves as a practical, innovative model for providing essential stunting prevention education to couples entering marriage.